Analysis of Fuel Spray Characteristics of Pertalite, Pertamax, and Pertamax Turbo with Ethanol Blending - Cholis, M. Iqbal; Noor, M. Fathuddin; Hakim, Lukman (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2024)
In the automotive industry sector, technological advances have entered the stage of using alternative fuels, and the principle of fuel injection in gasoline engines (electronic fuel injection), to create efficient fuel use and more environmentally friendly combustion. The method used in this research is an experimental method, namely a method used to test the characteristics of gasoline fuel with ethanol against spray using an injector. In this research, we will compare the characteristics of Pertalite, Pertamax, Pertamax Turbo gasoline spray, a mixture of ethanol and gasoline in different mixture variations. This test aims to analyze spray tip penetration, spray angle, and velocity of spray. The results of collecting spray tip penetration data resulted in the highest data value for Pertamax Turbo fuel mixed with 7% ethanol and the lowest for Pertalite fuel mixed with 7% ethanol. The results of the spray angle data collection had the highest value in the Pertamax 10% ethanol mixture and the lowest in the 5% ethanol mixture with Pertamax Turbo fuel. From the results of the Velocity of spray data processing, the highest value was found in the 10% ethanol mixture with Pertalite fuel and the lowest was the 5% ethanol mixture with Pertamax Turbo fuel. For ethanol mixtures, more attention must be paid to the complete spray or misting of the injected fuel. Mix the fuel with ethanol according to applicable standards. Always pay attention to chamber equipment to avoid leaks when collecting data